1995
DOI: 10.1136/gut.36.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Adenine arabinoside 5'-monophosphate in patients with chronic hepatitis B: comparison of the efficacy in patients with high and low viral replication.

Abstract: Differences in the populations studied could account for these discrepancies. In a previous study, we found that anti-HIV negative homosexuals with chronic hepatitis B seemed to respond as frequently as heterosexuals to ARA AMP treatment.3 In the same study, we found retrospectively that a low level of hepatitis B virus replication, as reflected by low serum hepatitis B virus DNA concentrations, was a factor for predicting response to ARA AMP.The aims of this study were to assess, in patients with chronic hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Therefore, chronic hepatitis B should be treated as early as possible in its natural course, before the HBV precore mutant becomes selected as the prevalent virus Bonino and Brunetto, 1993;Carman et al, 1993;Bertoletti et al, 19941. Experience with ARA-AMP therapy is still quite limited. In a study by Marcellin et al [1995], a complete and sustained response to ARA-AMP administration in chronic hepatitis B was seen only in a group of patients with low HBV replication (HBV DNA <lo0 pg/ml). In anti-HBe-positive patients, even with low levels of HBV DNA, sustained response was infrequent, in contrast to the case in HBeAg-positive patients.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, chronic hepatitis B should be treated as early as possible in its natural course, before the HBV precore mutant becomes selected as the prevalent virus Bonino and Brunetto, 1993;Carman et al, 1993;Bertoletti et al, 19941. Experience with ARA-AMP therapy is still quite limited. In a study by Marcellin et al [1995], a complete and sustained response to ARA-AMP administration in chronic hepatitis B was seen only in a group of patients with low HBV replication (HBV DNA <lo0 pg/ml). In anti-HBe-positive patients, even with low levels of HBV DNA, sustained response was infrequent, in contrast to the case in HBeAg-positive patients.…”
Section: Discussionmentioning
confidence: 97%
“…Before the demonstration of the efficacy of acyclovir on HSV infection, vidarabine and its more soluble derivative adenine arabinoside 5)-monophosphate (ara-AMP) have been considered the drug of choice for the treatment of herpes simplex encephalitis. The potent inhibitory effect on both HSV and HBV DNA polymerase activity as well as in primary duck hepatocytes, experimentally infected ducks and woodchucks [67,68,86], provided the rationale for clinical trials in chronic hepatitis B [87][88][89]. These studies have shown that a 4-week course of ara-AMP is effective in 30-50% of the patients in eradicating HBV replication, as assessed by the sustained disappearance of serum HBV DNA and HBeAg.…”
Section: Purine Analogsmentioning
confidence: 94%
“…axonal neuropathy associated with myalgia, seemed to prevail in longer courses (14 weeks) and in patients with preexisting electromyographic abnormalities. If one follows the recommendation to treat patients without electrophysiological abnormalities for no more than 4 weeks, ara-AMP is most often well tolerated and deserves consideration for antiviral therapy of chronic hepatitis B [87][88][89].…”
Section: Purine Analogsmentioning
confidence: 99%
“…Most studies have focused on chronic rather than acute hepatitis B infections. Drugs trialled or under trial include: the interferons [79][80][81][82], ribavirin [83,84], adenine arabinoside [85][86][87], gancidovir, penciclovir/famcidovir, fialuridine and other agents [88,89].…”
Section: ) Treatment Of Hepatitis Bmentioning
confidence: 99%